Immunization with the M12-N, M12-C, and M12-N+C fusion peptides derived from the M12 protein elicited varying levels of protective immune responses against multiple serotypes of group A Streptococcus - Zhang, Xiaolan; Ma, Yue; Na, Rige; Hou, Wenli; Hanski, Emanuel; Zhou, Qin (Frontiers in Immunology, 2025)
The M protein located on the surface of group A Streptococcus has been extensively researched as a promising vaccine candidate. However, issues such as potential cross-reactivity with human tissues and the impact of selection of M peptide sequences have raised concerns regarding the safety and efficacy of the M protein vaccine. In this study, we utilized a KSI (ketosteroid isomerase, 15.78 kDa) tag and conducted a comparative analysis of the N-terminal (M12-N, 28.14 kDa), C-terminal (M12-C, 30.24 kDa), and fusion form (M12-N+C, 29.19 kDa) derived from the M12 protein found in MGAS9429. Three vaccine candidates formulated with aluminum hydroxide adjuvant significantly increased specific antibody titers in serum following booster immunization. Furthermore, immunization with these vaccines improved the survival rates in mice challenged subcutaneously with MGAS9429 compared to control mice. The immune responses induced by our vaccine formulation were characterized by Th1 type responses marked by IFN-γ secretion rather than the Th2 type responses and a notable increase in effector memory T cells. Significantly, the vaccine candidate M12-C exhibited several advantages including shortened vaccination times, enhanced antibody levels, improved survival rates against non-vaccine serotype MGAS5005 challenge. Moreover, the M12-C antiserum demonstrated significant opsonization and killing effects on the non-vaccine strains of M1, M3, M6 and M18. This work identifies a promising fusion sequence of vaccine candidate when developing GAS vaccines based on M peptides to enhance immune responses and protective efficacy.